Tackling obesity and its complications in secure settings. Issue 1 (5th March 2014) - Long, Clive; Rowell, Arleen; Gayton, Anita; Hodgson, Elizabeth; Dolley, Olga
Abstract : Purpose: – The purpose of this paper is to explore the incidence of obesity and its complications in secure psychiatric settings; and to assess changes in body mass index (BMI). Design/methodology/approach: – Electronic patient records were used to determine levels of obesity and weight change over a three-year period. BMI levels were related to status, medication and patient characteristics. Findings: – The incidence of obesity (34 per cent) in the sample ( n =351) was higher than in the general population. One-third of patients were on medication for hyperlipidaemia and 10 per cent were diagnosed with type II diabetes. Patients on regular antipsychotic drugs and sodium valproate and who were less active had higher BMIs. Gender differences over a three-year period showed a tendency for women's weight to continue to increase which may be linked to lower levels of engagement in activities of moderate or vigorous intensity. Originality/value: – Previous surveys using secure psychiatric populations have been point in time reviews. The current study tracks changes over a three-year time period and related this to a range of interventions.